2004
DOI: 10.1091/mbc.e03-10-0743
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Functional Domains within Nucleoporins Nup153 and Nup98 Mediate Transcription-dependent Mobility

Abstract: Despite the apparent overall structural stability of the nuclear pore complex during interphase, at least two nucleoporins have been shown to move dynamically on and off the pore. It is not yet certain what contribution nucleoporin mobility makes to the process of nuclear transport or how such mobility is regulated. Previously, we showed that Nup98 dynamically interacts with the NPC as well as bodies within the nucleus in a transcription-dependent manner. We have extended our studies of dynamics to include Nup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
104
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(118 citation statements)
references
References 43 publications
13
104
1
Order By: Relevance
“…Initially, a subset of Nups was found to be mobile, able to move off and on the pore (16). The intranuclear accumulation of one such Nup, Nup98, is linked to ongoing nuclear transcription and chemical inhibition of RNA polymerase II was shown to abrogate its intranuclear mobility (17,18). Moreover, Nup98 was subsequently found to directly control gene expression of a subset of developmentally regulated genes (19)(20)(21).…”
mentioning
confidence: 99%
“…Initially, a subset of Nups was found to be mobile, able to move off and on the pore (16). The intranuclear accumulation of one such Nup, Nup98, is linked to ongoing nuclear transcription and chemical inhibition of RNA polymerase II was shown to abrogate its intranuclear mobility (17,18). Moreover, Nup98 was subsequently found to directly control gene expression of a subset of developmentally regulated genes (19)(20)(21).…”
mentioning
confidence: 99%
“…A cell needs to accurately segregate not only the genetic material and all the organelles but also the NE membranes with its specific protein components. According to the ERretention model (Collas and Courvalin, 2000), some NE components are retained in the mitotic ER network during cell division, but numerous other ones localize to diverse mitotic structures and play crucial roles in consecutive stages of the division process (Rabut and Ellenberg, 2001;Griffis et al, 2004;Xu et al, 2008;Lee et al, 2009). Both the localization patterns and a variety of developmental phenotypes point to these functions.…”
Section: Dual Roles Of Ne Components During Mitosismentioning
confidence: 99%
“…Tobacco NbRae1, a homolog of Rae1/mrnp41 in metazoans, Gle2p (for GLFG lethal 2p) in Saccharomyces cerevisiae, and Rae1 in Schizosaccharomyces pombe, exhibits a mitotic function besides its role as an mRNA export factor associated with the NPC (Whalen et al, 1997;Pritchard et al, 1999;Griffis et al, 2004;Lee et al, 2009). Mammalian Rae1 is a mitotic spindle checkpoint component in conjunction with Bub3 and forms a complex with Nup98 and the Cdh1-activated anaphasepromoting complex, preventing the degradation of Securin before anaphase (Whalen et al, 1997;Babu et al, 2003;Jeganathan et al, 2005).…”
Section: Metaphasementioning
confidence: 99%
“…Nup153 has also been found to be essential for the localization of other pore components (19) and is specifically thought to anchor the basket constituent TPR (20). Somewhat paradoxically, Nup153 has been shown to be dynamically localized to the nuclear pore (21,22). This apparent contradiction, as well as the multiple roles implicated for Nup153, may be reconciled by the presence of distinct populations of this pore protein.…”
mentioning
confidence: 99%
“…Indeed, an analysis of Nup153 mobility indicated that a fraction of Nup153 is stably associated with the pore (Ref. 22, see also Ref. 21).…”
mentioning
confidence: 99%